Nang Mauso ang Pagpapantasya: Isang Pag-aaral sa Estado ng Kababalaghan sa Telebisyon - Yapan, Alvin B. (Plaridel Journal of Communication, Media, and Society, 2011)
This study looks into the dynamics of fantasy in the so-called telepantasya or pantaserye, particularly in how it uses the concept of space. It shows how the worlds of reality and fantasy are differentiated in these locally-produced television series. Encantadia and Majika on GMA 7, and Super Inggo and da Adventures of Pedro Penduko on ABS-CBN 2 are analyzed for this purpose. An in-depth analysis of these shows leads the writer to conclude that there are many elements of "fantastic narratives" adapted from the West, particularly the dichotomy between reality and fantasy. This dichotomy is not found in Philippine mythology, where the 'mysterious' (kababalaghan) coexists with and impinges on the real.